Potentials of Antitussive Traditional Persian Functional Foods for COVID-19 Therapy† - Mosleh, Ghazaleh; Badr, Parmis; Zaeri, Meysam; Mohagheghzadeh, Abdolali (Frontiers in Pharmacology, 2021)
Coronavirus disease 2019 is a worldwide pandemic resulting in a severe acute respiratory syndrome. Remdesivir is the only FDA-approved drug for hospitalized patients older than age 12. It shows the necessity of finding new therapeutic strategies. Functional foods (FFs) could have co-therapeutic and protective effects against COVID-19 infection. Traditional Persian medicine (TPM), one of the safest and most popular schools of medicine for hundreds of years, has recommended potential FF candidates to manage such a global pandemic. To reveal the potential of TPM in terms of antitussive FFs, traditional Persian pharmacopoeia “Qarabadin-e-Salehi” was searched using the keywords “Soaal” and “Sorfeh.” Also, a search of MEDLINE, PubMed Central, Google Scholar, and Science Direct was performed for the relevant literature published from the inception up to March 2021. A combination of search terms including “cough, antitussive, antioxidant, anti-inflammation, antiviral, COVID-19, mucoactive, mucolytic, expectorant, and mucoregulatory” was also applied. The potential mechanism of action in SARS-CoV-2 infection was discussed. Twelve TPM FFs were found including Laooqs, Morabbas, a Saviq, a soup, and a syrup. They are combinations of two to seven ingredients. Natural compounds of mentioned formulations have the main pharmacological mechanisms including antiviral, anti-inflammatory, antioxidant, antihistamine, bronchodilator, immunomodulatory, and mucoactive effects as well as central or peripheral antitussive activities. FFs are cost-effective, easily accessible, and safe options for both treatment and prevention of COVID-19. They might have positive psychological effects along with their pharmacological effects and nutritional virtues. They could also manage persistent respiratory discomforts after recovery from COVID-19.